DNA Methylation of miR-122 Aggravates Oxidative Stress in Colitis Targeting SELENBP1 Partially by p65NF-κB Signaling. (24th March 2019) - Bai, Jianan; Yu, Junchi; Wang, Jintian; Xue, Bingyan; He, Na; Tian, Ye; Yang, Lixia; Wang, Yipin; Wang, Yanyan; Tang, Qiyun
Abstract : Aberrant microRNA (miRNA) expressions contribute to the development and progression of various diseases, including Crohn's disease (CD). However, the accurate mechanisms of miRNAs in CD are definitely unclear. We employed colonic tissue samples from normal volunteers and CD patients, an acute mice colitis model induced by 2, 4, 6-trinitro-benzene-sulfonic acid (TNBS), and a cellular oxidative stress model induced by H2 O2 in HT-29 cells to determine the effects of oxidative stress on expressions of miR-122, selenium-binding protein 1 (SELENBP1, SBP1), p65 nuclear factor κ B (p65NF- κ B) signaling, and DNA methylation. We found that SBP1 was mainly located on epithelial cells and was significantly increased in patients with active CD. SBP1 was the target gene of miR-122. miR-122 expression was downregulated while SBP1 expression was upregulated under TNBS-induced colitis or oxidative stress. Pre-miR-122 or siRNA SBP1 (si-SBP1) treatment ameliorated acute TNBS-induced colitis and H2 O2 -induced oxidative stress. Cotreatment of pre-miR-122 and si-SBP1 enhanced these effects. Besides, pre-miR-122 and si-SBP1 obviously activated the p65NF- κ B signaling by phosphorylation of I κ B α . Bisulfite sequencing of the CpG islands in the promoter region of miR-122 showed that CpG methylation was significantly increased under oxidative stress. Treating cells with 5 ′ -AZA which was well known as a DNA-demethylating agent significantly increased miR-122 expression. Our results suggest that oxidative stress-induced DNA methylation of miR-122 aggravates colitis targeting SELENBP1 partially by p65NF- κ B signaling and may promote the progression of CD.